Chebulinic acid suppresses porcine epidemic diarrhea virus infection by inhibiting viral entry and viral main protease - Li, Zhonghua; Huang, Yizhi; Zhang, Yi; Zhao, Di; Wang, Lei; Wang, Zhanchang; Hu, Qunbing; Yang, Ling; Wu, Tao; Hou, Yongqing (Frontiers in Cellular and Infection Microbiology, 2025)
Porcine epidemic diarrhea virus (PEDV) has resulted in significant economic losses in the global swine industry, making the development of effective therapeutic approaches a pressing need. In this study, we found that chebulinic acid significantly restrained PEDV replication in CCL-81 and LLC-PK1 cells, demonstrated by reductions in viral genome, viral protein, and titer. Molecular docking analysis made it clear that chebulinic acid might bind the key amino acids of binding pocket and the active center of PEDV main protease. Subsequent in vitro experiments confirmed the inhibitory effects of chebulinic acid on PEDV main protease, with an IC50 value of 61.53 ± 2.12 μM determined through a fluorescence resonance energy transfer (FRET) assay. Additional investigations demonstrated that chebulinic acid could inhibit the attachment and penetration processes of PEDV infection. Overall, our results provide experimental evidence supporting the inhibitory effects of chebulinic acid on PEDV infection by targeting viral entry and the inhibitory effects on main protease. The results of this study offer potential for creating new treatments for porcine epidemic diarrhea.